HRM Strategy: A Way To Create Organizational Performance In Achieving Competitive Advantage - Yuliana, Novita (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
Human Resource Management (HRM) strategies are critical factors in creating superior organizational performance and sustainable competitive advantage. This study aims to analyze how strategic HRM practices can serve as the primary driver of organizational success amid increasingly complex business competition. Using a qualitative approach with a systematic literature review method, this study examines various academic sources related to HRM strategies, organizational performance, and competitive advantage. The findings reveal that the implementation of comprehensive HRM strategies, including competency-based recruitment, continuous employee development, performance-based compensation systems, transformational leadership, and 360-degree performance evaluations, significantly contributes to improved productivity, innovation, and organizational competitiveness. These findings reinforce the Resource-Based View (RBV) theory, which positions human resources as a strategic asset that is valuable, scarce, and difficult to imitate. The study also identifies the key role of a collaborative organizational culture and transparent feedback systems in enhancing the effectiveness of HRM practices. The practical implications of this research emphasize the need for alignment between HRM strategies and long-term business objectives, as well as the importance of adapting to changes in the business environment. This research contributes to the development of HRM literature by presenting an integrated synthesis of the mechanisms linking HRM practices, organizational performance, and competitive advantage. Suggestions for future research include empirical exploration of HRM strategy implementation in specific industry contexts and the impact of digital transformation on HRM effectiveness.